A rare case of acute pancreatitis due to scrub typhus: A case report - Nitesh Badal; Chiranjita Phukan; Bipul Chandra Kalita; Sangitanjan Dutta (Assam Journal of Internal Medicine)
Scrub typhus is an acute febrile sickness, also known as tsutsugamushi fever, which is brought on by Orientia tsutsugamushi, a tiny, obligate intracellular gram-negative bacteria whose polysaccharides have an antigenic connection to proteus OX-K, which is utilised in serologic tests to confirm scrub typhus. The larva of trombiculid mites (chiggers), which are almost minute and frequently brilliantly colourful (red), bite people to transmit O. tsutsugamushi. The signs of onset include fever, headache, myalgia, coughing, and gastrointestinal symptoms after an incubation period of 6–21 days. The primary papular lesion, which the chigger fed on and can appear anywhere on the body, enlarges, experiences core necrosis, and crusts to create a flat black eschar. Regional lymphadenopathy and later generalised lymphadenopathy can be found. A macular rash may develop on the trunk, and the symptoms gradually worsen. In untreated cases, complications may develop and patient may have meningoencephalitis and at times, multiple cranial nerve deficits.